Destination management and sustainable development through the common lens of the commons - Jo\~ao Rom\~ao; Mayumi Okada; Kazuo Machino; Peter Nijkamp (REGION, 2021)
This study combines three interconnected streams in tourism literature: analysis of the utilisation of common pool resources (CPR) in tourism, studies on sustainable tourism development and theoretical contributions to the articulation of roles, missions and strategies of a destination management organisation (DMO). Starting from an integrative literature review, our aim is to explore the symbiotic relationships between these approaches in order to design a conceptual framework that opens new research opportunities. Clearly, the concrete application of such a conceptual model depends on the resources of each destination, the type of tourism dynamics observed, the specific stakeholders involved and the power balance between them. Our approach integrates the principles of sustainable development into the strategic role of a DMO through the management of CPR, aiming at the achievement of significant benefits for the host communities within the three pillars of sustainable development (ecological, social and economic) through participatory processes of destination management. In addition, we present an exploratory illustration of this conceptual framework for the case of a rural destination of Kushiro-Akan (Hokkaido, Japan). Policy and managerial implications are discussed, along with the needs for further research.
Keywords: 330; common pool resources; destination management organisation (DMO); sustainable development; participatory governance